1997
DOI: 10.1113/expphysiol.1997.sp004039
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Mg(2+)ࢤselective macroelectrodes down to 1 mumol lߝ1 in intracellular and Ca(2+)ࢤcontaining extracellular solutions

Abstract: 4.5 and 3, respectively). At present, measurement of the Kapp and ligand purity in the appropriate solution at the desired pH and temperature would seem to be the best strategy to adopt rather than attempting to calculate the constant. Since no recognized international standard exists for [Mg2+] at the micromolar level, values in the literature for Kd, etc. in this range can only be regarded as approximate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…1 for the estimated [Ca 2+ ] for all four buffers because all lie on the same calibration curve. In view of these findings and previous ones [4,13], it can be concluded that the ligand optimization method accurately estimates the [Ca 2+ ] and [Mg 2+ ] in buffer solutions.…”
Section: Ligand Optimization Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…1 for the estimated [Ca 2+ ] for all four buffers because all lie on the same calibration curve. In view of these findings and previous ones [4,13], it can be concluded that the ligand optimization method accurately estimates the [Ca 2+ ] and [Mg 2+ ] in buffer solutions.…”
Section: Ligand Optimization Methodsmentioning
confidence: 71%
“…First, the ligand optimization method [4] is a robust and accurate method to determine both K app and ligand purity. Second, there is no agreement between calculated and measured [Ca 2+ ] in EGTA, BAPTA, HEDTA, and NTA buffers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(: p. 361) described six criteria for an ideal method to measure [X 2+ ] in buffer solutions. Of the seven methods investigated (McGuigan et al., : table 4), only two met all six criteria, namely, the LOM (Lüthi, Spichiger, Forster, & McGuigan, ) and setting concentrations by dilution from 2 mmol l −1 to 10 −7 mol l −1 (Allen, Blinks, & Prendergast, ). The LOM is a routine method and is explained in detail in the Supporting Information.…”
Section: Introductionmentioning
confidence: 99%
“…Several carriers ETH 5282 [15], ETH 5214 [1a, 20, 22, 32], ETH 5250 [18,28], ETH 7025 [17,21,22,24,29], ETH 3832 [27,33], ETH 5506 [21,33], and the derivative of o-phenanthroline [30], have now been used in potentiometric clinical analysis. The apparent influence of calcium has to be compensated for by numerical techniques for most of the sensors specifically in the extracellular space where the Ca 2þ -exceeds the Mg 2þ -molality by a factor of ca.…”
Section: Introductionmentioning
confidence: 99%